2018
DOI: 10.3389/fendo.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NOD Mice in Type 1 Diabetes Research: Lessons from the Past and Recommendations for the Future

Abstract: For more than 35 years, the NOD mouse has been the primary animal model for studying autoimmune diabetes. During this time, striking similarities to the human disease have been uncovered. In both species, unusual polymorphisms in a major histocompatibility complex (MHC) class II molecule confer the most disease risk, disease is caused by perturbations by the same genes or different genes in the same biological pathways and that diabetes onset is preceded by the presence of circulating autoreactive T cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 138 publications
4
101
0
Order By: Relevance
“…Intraperitoneal glucose tolerance tests were performed at the age of 13-14 weeks. The results confirmed several well-known strain-specific characteristics, such as impaired glucose tolerance in NZO/HILtJ and NOD/ShiLtJ mice (Chen et al 2018;Kleinert et al 2018) and references therein) (GMC11, data not shown). In contrast, 129S1/SvImJ mice showed very low basal fasting glucose levels and low AUC values, which is in line with the observation of low endogenous glucose production in fasting 129S1/SvImJ mice (Burgess et al 2005).…”
Section: Glucose Tolerance Testsupporting
confidence: 86%
“…Intraperitoneal glucose tolerance tests were performed at the age of 13-14 weeks. The results confirmed several well-known strain-specific characteristics, such as impaired glucose tolerance in NZO/HILtJ and NOD/ShiLtJ mice (Chen et al 2018;Kleinert et al 2018) and references therein) (GMC11, data not shown). In contrast, 129S1/SvImJ mice showed very low basal fasting glucose levels and low AUC values, which is in line with the observation of low endogenous glucose production in fasting 129S1/SvImJ mice (Burgess et al 2005).…”
Section: Glucose Tolerance Testsupporting
confidence: 86%
“…There are many other chemokines that probably play redundant roles in the recruitment of T cells to the islets, including CXCL16 and its receptor CXCR6. This chemokine ligand-receptor pair is of particular interest in T1D, as CXCL16 is a potential candidate gene for the Idd4 T1D risk locus in mice, and CXCR6 is located within the IDDM22 T1D risk locus in humans [93][94][95][96]. In our work, CXCR6 was the highest chemokine receptor mRNA transcript expressed in islet T cells, and CXCL16 was the third highest expressed chemokine transcript in islet CD11c + cells [13].…”
Section: Chemokines In T Cell Trafficking To the Isletsmentioning
confidence: 80%
“…A previous work demonstrated the therapeutic potential of PS-liposomes encapsulating insulin peptidesas a main autoantigen in T1Dto prevent T1D in an experimental model of the disease, the Non-Obese Diabetic (NOD) mouse [8]. The NOD mouse, developed in 1980 [9] is considered the 'gold-standard' model for the study of T1D [10]. These mice develop T1D spontaneously around 12 weeks of age, after the immune-mediated destruction of insulin-producing b cells, commonly called insulitis.…”
Section: Introductionmentioning
confidence: 99%